Redukcjonizm w twórczości fletowej Henryka Mikołaja Góreckiego z lat 1986–1996 - Kassner, Weronika (Res Facta Nova, 2021)
The aim of this discussion is to demonstrate manifestations of reductionism in the works of Henryk Mikołaj Górecki. In order to achieve this the article compares conclusions based on analyses of three works for the flute by Górecki composed during the same decade – For you, Anne-Lill op. 58 for flute and piano (1986), Good Night op. 63 for soprano, alto flute, piano and three tam-tams (1990) as well as Valentine Piece op. 70 for flute and bell (1996). The part of the flute is analysed in particular detail – the way it is shaped, its type of narration, and its relation to other instruments. The article is in two parts: the first outlines the tendencies in flute compositions in 20 th century in Poland and in the world, while the second part presents analyses of selected flute compositions by Górecki. The conclusions point to Górecki having an individual approach to using the flute as a solo instrument or as part of a group of instruments in a chamber composition, as well as to cohesiveness of the development of flute compositions against the background of the composer’s stylistic evolution as a whole.